Pensions as Retirement Income Insurance - Bodie, Zvi (Journal of Economic Literature, 1989)
This paper develops the view that employer-sponsored pension plans are best understood as retirement income insurance for employees and from that perspective addresses a number of questions regarding the reasons for their existence, their design, and their funding and investment policies. The most important of these questions are: - Why do employers provide pension plans for their employees and why is participation usually mandatory? - Why is the defined benefit form of pension plan the dominant one rather than defined contribution? - Why are the payout options under most plans limited to life annuities? - Why are most plans integrated with Social Security? - Why don't corporate pension plans follow the extreme funding and asset allocation policies that seem to be optimal from the perspective of shareholder wealth maximization? - Why do employers often make ad hoc increases in pension benefits not strictly required under the formula in defined benefit plans? - Why don't private pensions offer inflation insurance?